PENEGAKAN HUKUM DALAM PEMBERANTASAN TINDAK PIDANA JUDI ONLINE (JUDI SLOT) DIKOTA TALUK KUANTAN: Penegakan Hukum yang Dilakukan Oleh Kepolisian Resort Kabupaten Kuantan Singingi, Hambatan Yang Dihadapai Dalam Penegakan Hukum Tindak Pidana Perjudian Online Oleh Kepolisian Resort Kota Taluk Kuantan, Upaya Yang Dilakukan Oleh Kepolisian - Riska Sahfitri (Jurnal Hukum Lex Generalis, 2023)
Empirical research is the research method used. Primary and secondary data sources form research data sources. The formulation of the problem in this research is what are the actions of law enforcement in eliminating illegal online gambling (slot gambling) in Kuantan Singingi? and what are the obstacles to law enforcement efforts to crush illegal on-line gambling (slot gambling). Research findings show that Law enforcement used criminal efforts to eradicate illegal online gambling (also known as “slot gambling”) in Kuantan Singingi after crimes were committed under the criminal code. There are challenges facing Kuantan Singingi Regency law enforcement in their efforts to crush illegal internet gambling (slot gambling).